1977
DOI: 10.1111/j.1651-2227.1977.tb07955.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Septicaemia in the Newborn Infant: Choice of Initial Antimicrobial Drugs and the Role of Exchange Transfusion1

Abstract: The therapeutic success of antibiotics used at the beginning of treatment and the effect of exchange transfusion in cases of septicaemia were tested in 22 newborn infants. The clinical course of these patients was compared with the outcome of 11 newborn infants who received antibiotic treatment without exchange transfusion. The following results were obtained: 1) All 6 patients initially receiving antibiotics, which were ineffective in vitro, died. In this group of patients the incidence of septic organ involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Two hours after the sponge had been implanted, no detectable diminution in storage neutrophils had occurred, but by 6 h the quantity of reserve neutrophils had been reduced to 16 a 8% (mean a 2SD) of the initial level, indicating that 84 a 8% of the neutrophil supply had been released. At 20,24, and 48 h following sponge implantation, storage neutrophils remained at a similarly low level, but at 120 and 144 h, increases were observed. In order to detect bacterial contamination of sponge implants, 10 animals were sacrificed 6 h after sponge implantation and sponges were removed for bacterial culture.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Two hours after the sponge had been implanted, no detectable diminution in storage neutrophils had occurred, but by 6 h the quantity of reserve neutrophils had been reduced to 16 a 8% (mean a 2SD) of the initial level, indicating that 84 a 8% of the neutrophil supply had been released. At 20,24, and 48 h following sponge implantation, storage neutrophils remained at a similarly low level, but at 120 and 144 h, increases were observed. In order to detect bacterial contamination of sponge implants, 10 animals were sacrificed 6 h after sponge implantation and sponges were removed for bacterial culture.…”
Section: Resultsmentioning
confidence: 89%
“…Because of the frequently disappointing result when neonatal sepsis is treated with antibiotics alone, investigators have suggested that adjunctive measures, such as exchange transfusion (24,25), granulocyte transfusion (2, 8, 9, 15), or antibody administration (5, 10, 13, 2 1, 22) should be tested. While some studies suggest that each of these approaches might have merit, it is currently unclear which, if any, of these measures should be employed in various clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…Xanthou et a1 [36] also found a marked diminution in phils to septic neonates, Tollner et a1 [33] and Vain et a1…”
Section: Discussionmentioning
confidence: 90%
“…Despite these theoretical benefits, evidence for clinical efficacy and safety of DVET has not been rigorously evaluated. Out of 11 controlled trials (3 randomized and 8 non-randomized) done in 570 neonates, six have shown a significant improvement in survival in the DVET group in comparison to no DVET [5][6][7][8][9][10][11][12][13][14]. However, all studies were heterogeneous with regards to patient characteristics, eligibility criteria, stage and severity of sepsis at enrollment, study design and steps taken to minimize the bias, type of blood used and outcomes analyzed.…”
Section: Introductionmentioning
confidence: 99%